Penerapan Pembelajaran Tematik dengan Model Webbed untuk Mengukur Kemampuan Komunikasi Matematis Siswa - Zaky Ghufron; Goenawan Roebyanto; Sri Harmini (Faculty of Education Universitas Negeri Malang, 2017)
Abstact: The purpose of this study is to improve the learning situation in the third grade of elementary school that the learning is not in accordance with the learning set by the Curriculum 2006 and does not pay attention to students’ mathematical communication ability. Therefore, this study applies thematic learning with webbed model to measure students’ mathematical communication ability. The type of research used is classroom action research, and implemented in one cycle. This classroom action research was conducted in MI Nurul Huda Sadar Sriwijaya Lampung Timur with the subject of third grade student research which amounted to 35 students. The results showed that classroom action research with the central theme